Reglas de juego y su influencia en el desenvolvimiento teórico, táctico del futbol en las categorías sub 10-14 de los jugadores del Club Nueva Generación de la Parroquia San Carlos - Barco Lojano, Karem Katherine (2019)
This research contains an important aspect of the impact generated by the rules of the game which is very fundamental when playing football, it helps us to facilitate the technical, tactical, disciplinary performance of athletes, the consequences that cause their inappropriate behavior both with his teammates, opponents, and referees. In this sense, the degree of knowledge of this was characterized, which revealed theoretical limitations in coaches and players. This framed the intentionality of designing a strategy in terms of game rules brochures. For the development of this research, it was based on the quasi-experiment modality, starting from a direct observation with the object of study, as well as the interpretation of the problem, the implementation of an evaluation of the tactical conditions of the training sessions of the players. The valuation of its relevance under a series of surveys conducted on knowledge, expressed its acceptance of this proposal. In the same way, the results obtained during the partial practice, allowed us to corroborate the effectiveness of the strategy since it was possible to implement game rules that benefit the new generation club players and their coaches.